Students' Difficulties in Converting Active Sentences into Passive Sentences in Simple Tense at MAN 3 Solok Students - Sari, Wita Purnama; Melani, Melyann; Nurhayanis, Nurhayanis (Journal of Educational Management and Strategy, 2024)
This research was motivated by the minimal score of students got when did quiz about passive voice in simple tense. That was why the research about analysis of students’ difficulties in changing active sentence became passive sentence in simple tense was crucial to done. The aim of this research was to find out the students difficulties in changing active sentence become passive sentence in simple tense form on social student's one of elevent grade of MAN 3 Solok. There were thirty four students but twenty students only choosen as informant of this research. This research used descriptive qualitative method and the source of the data was paper of students’ original answer about passive voice in simple tense. The miles and Hubermans’ model was technic of analysis data used in this research. There were several difficulties got on students in changing active sentence became passive sentence in simple tense as result. The first difficulty was students difficult to used correct auxalary verb (to be) in passive actually in simple past tense. Next difficulty was students difficult to analyze the subject in the sentence, students confused did the subject singular or plural.The other difficulty was students difficult to decide the object correctly. The last difficulty was students difficult to change verb one and verb two became verb three.